Analisis Wacana Kritis Berita “Mahfud MD: Pemerintah Tak Setengah-Setengah Tindak Pelaku Investasi Ilegal” di Kumparan.com - Abu Setiawan Pratama; Ferry Darmawan (UNISBA Press, 2022)
Abstract. Illegal investment under the guise of binary options is currently being discussed in the community. This issue has also become the main topic of news coverage in online news portal in Indonesia. The online news portal Kumparan is one of the online news portal that reports about this case of illegal binary options investment. The discussion about illegal binary options investment is inseparable from the two cases of arresting influencers who were caught in illegal investment cases. The first case ensnared Indra Kesuma who was proven guilty of fraudulent binary options investment through the Binomo application. Then, the second case ensnared Doni Salmanan who was also proven to have committed a binary option investment fraud through the Quotex application. This study uses a descriptive qualitative research method with a critical paradigm approach. The researcher will use the theory of Critical Discourse Analysis of the Teun A. Van Dijk model by taking one of the news uploaded on the online news portal Kumparan entitled